Chemical profile and phytotoxic action of Onopordum acanthium essential oil - Caixia Wei (Nature Portfolio, 2020)
Abstract The potential of utilizing Onopordum acanthium essential oil and its major constituents as environment friendly herbicides was investigated. In total 29, 25, and 18 compounds were identified from flower, leaf, and stem oils, representing 94.77%, 80.02%, and 90.74% of the total oil, respectively. Flower and stem oils were found to be rich in n-alkanes, which accounted for 57.33% in flower oil, and 82.33% in stem oil. Flower oil exerted potent inhibitory activity on both receiver species, Amaranthus retroflexus and Poa annua, which nearly completely suppressed seed germination at 5 mg/mL, and β-eudesmol is the most likely responsible compound for its phytotoxicity; in comparison, leaf and stem oils exhibited much weaker inhibitory activity on A. retroflexus, and stimulatory effect on P. annua when tested concentration was below 2.5 mg/mL. Alkanes in the oils were found to exert relatively weak plant growth regulatory activity. This report is the first on the chemical profile and phytotoxic action of O. acanthium oil as well as the phytotoxicity of β-eudesmol.